Muskox and Man in the Central Canadian Subarctic 1689-1974 - Burch, Jr., Ernest S. (ARCTIC, 1977)
Discusses the significance of muskoxen in the lives of native peoples in the Canadian Subarctic. Muskoxen were killed for meat and for furs by the Chipewyan and the Inuit in what is now the southern portion of the District of Keewatin, N.W.T., and the northern portion of Manitoba during the years of study.